The Importance of Literacy to Avoid Indonesian Younger from Hoaxes Spread - Abdussalam, Muhammad Rafi; Alamsyah, Fatra (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2021)
Developments in the field of information technology are one of the scientific and technological advances that are developing quickly in the globalization era. This growth should be capitalized on, particularly by the younger generation as a contender for the nation's successor, in order to promote the country. However, because to the ease of access to social media, hoaxes are becoming increasingly common in many sectors of life, particularly among the younger generation (almost all social media users are young people). Hoaxes are becoming more common as a result of young people's tendency of drawing conclusions from news headlines without first confirming the legitimacy and accuracy of the material. Furthermore, the lack of literacy knowledge in obtaining clarification about a hoax has resulted in the rapid development of hoaxes. The problem faced by Indonesia is the low literacy mastery as evidenced by the Program for International Student Assessment (PISA) survey. As a result, it is worthwhile to address the role of reading literacy in conquering critical thinking to prevent the development of hoaxes in Indonesia. The younger generation need critical thinking skills to weed out false information. Literacy must be instilled as early as possible since it is the key capital in achieving an educated and cultural nation. The writing takes a normative approach, with reading materials drawn from respectable journals, books, and online sites on the subject.